2017
DOI: 10.4314/jfas.v9i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antibacterial and cell toxicity effects of polyphenols <i>Fromahmeur bouamer</i> grape seed extracts

Abstract: In this work and for the first time, significant concentrations of total polyphenols and flavonoids from Vitis vinifera L. grape seed extracts were obtained (256.15 ± 17.40 mg GAE/g dm and 14.08 ± 0.64 mg CE/g dm , respectively).The LC/MS analysis revealed richness in procyanidins. For antioxidant, antimicrobial and antifungal effects, the grape seed extract (GSE) responded positively. At 100 μg/mL, GSE induced a moderate toxicity of the order of 3.88% on 3T6 cells at the first 24 hours of treatment, whereas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The method proposed by Ghouila et al () was followed with slight modifications for the extraction process. Briefly, an appropriate amount of dry powder of each plant was dissolved in 100 mL acidified aqueous ethanol (0.1% HCl, v/v) consisted of different ethanol proportions ranged from 0 to 100% (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…The method proposed by Ghouila et al () was followed with slight modifications for the extraction process. Briefly, an appropriate amount of dry powder of each plant was dissolved in 100 mL acidified aqueous ethanol (0.1% HCl, v/v) consisted of different ethanol proportions ranged from 0 to 100% (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Then, the absorbance was recorded at 517 nm. The ABTS· + scavenging capacity was measured according to Ghouila et al, () with some modifications. The ABTS (170 μl) solution with an absorbance at 734 nm of 0.7 ± 0.2 was mixed with 30 μl of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Negro et al [ 25 ] reported that the total phenols (gallic acid equivalent (GAE)), total flavonoids (catechin equivalent (CE)), catechin equivalent (CE), and proanthocyanidins (cyanidin equivalent (CyE)) in red grape seed extracts were 8.58 g/100 g dry matter (DM), 8.36 g/100 g DM, 6.41 g/100 g, DM and 5.95 g/100 g DM, respectively. Another study by Ghouila et al [ 26 ] documented that the total phenolic content and total flavonoid content of Ahmeur Bouamer grape seeds were 265.15 mg GAE/g of dry mass and 14.08 mg catechin equivalent (CE)/g of dry mass, respectively.…”
Section: Phytochemical Compounds In Grape Seedsmentioning
confidence: 99%
“…In addition, the authors demonstrated that these extracts completely inhibited Gram-positive bacteria and Gram-negative bacteria at 850–1000 ppm and 1250–1500 ppm, respectively. A study by Ghouila et al [ 26 ] demonstrated that grape seed extracts exhibited antimicrobial activity to Microccocus luteus ATCC ® 9341, S. aureus ATCC ® 29213, E. coli ATCC ® 25992, P. aeruginosa ATCC ® 27853, Aspergillus niger , and Fusarium oxysporum , with a diameter of the inhibition growth zone ranged from 15–20 mm.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%